The Influence of Capital Structure and Sales Growth on Profitability at PT Mayora Indah Tbk From 2017 to 2024 - Nafralli, Vianka Zahra; Tambi, Chika Febrine; Manurung, Elizabeth Tiur (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
In the modern business world, companies are required to have strong and stable financial performance to maintain operational sustainability while winning market competition. Profitability is a key indicator that shows a company's ability to generate profits from its assets or capital. Therefore, an analysis of the factors that influence profitability is important to understand. One such internal factor is capital structure, which refers to the ratio between debt and equity in a company's financing. This st.udy aims to ana.lyze the effect of capital structure and sales growth on the profitability of PT Mayora Indah Tbk for the period 2017–2024. The method used is descriptive- verificative quanti.tative rese.arch with secondary data from financial reports. The analysis w.as co.ndu.cted using mul.tiple line.ar regr.ession and clas.sical assumption tests. The normality test results show that the data is normally distributed (Sig. 0.200 > 0.05), there is no multicollinearity (VIF 6.402), and there is no heteroscedasticity (Sig. > 0.05). The regression results show that capital structure has a positive and significant effect on profitability (coefficient 0.441; t count 7.652; Sig. 0.000). Sales growth also has a positive and significant effect (coefficient 0.408; t count 5.479; Sig. 0.000). Simultaneously, both variables h.ave a signif.icant eff.ect w.ith an F value of 530.047. The R Square value of 0.995 ind.icates that 99.5% of the va.riation in profitability is explained by these two variables. This study concludes th.at cap.ital stru.cture and sales growth play an important role in increasing company profitability.